(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
There was defined modern problems of the stable land use in Ukraine, analysed the structure of lands with different functions be numbered among The Land Fund of Ukraine by the state on January, 1, 2015, realized the comparison of Ukrainian agricultural lands and those ones in the Western Europe. During the 1994–2012 it was described the existing changes, determined the reasons, suggested the ways of intensification for land use based on the regional peculiarities